Identification of Cattle Using Nasolabial Plate Imprints and Biometric Analysis - Daniel Špoljarić; Luka Pajurin; Megi Kujundžić; Maja Ferenčaković; Anja Vrbaški; Branimira Špoljarić; Gordan Mršić; Mirela Pavić Vulinović; Marko Samardžija; Maja Popović; Silvijo Vince (Veterinary Medicine and Science)
ABSTRACT Background Animal identification is a topic of many studies, with a range of biometric methods currently in use. The cattle muzzle serves as a unique source of biometric traits. Objectives The aim of this study was to determine the best method for muzzle visualisation using imprints, the most frequent forms and minutiae points on imprints, and the minimum number of minutiae points required to establish an identity profile. Methods Noseprints of 30 calves were taken on different surfaces and visualised using different methods (white paper and cardboard/ninhydrin solution and glass tile/small particle reagents and ceramic tile/fluorescent powder and glossy photopaper/grey instant or magnetic powder). The imprint of the entire muzzle was photographed and analysed using the Automated Fingerprint Identification System (AFIS) to detect the most frequent forms based on friction ridges and minutiae points. Further mathematical simulation revealed the minimal number of points required for animal identification. Results The best imprint was obtained on glossy black photopaper with grey instant powder. After analysing the digitised images with the AFIS magnifier, the six forms of beads and ridges in the selected 12 minutiae points were detected, thus creating an identity chart. Computer simulation confirmed that the lowest number of minutiae points necessary for unique animal identification, and 0% possibility of form repetition at points, was nine of the 12 selected points. Conclusion As a biometric method, the muzzle imprint in combination with AFIS has the potential to be stored on large scale and used internationally, enabling identity control that is not susceptible to the issues involved with other biometric methods.